Gender, time-use, and energy expenditures in rural communities in India and Nepal - Picchioni, Fiorella; Zanello, Giacomo; Srinivasan, C. S.; Wyatt, Amanda; Webb, Patrick (Elsevier, 2020)
Women’s patterns of time-use, which proxy the work burdens associated with productive and reproductive activities, are an important determinant of nutrition and well-being in LMICs. However, there is a lack of empirical evidence on how patterns of time-use translate into patterns of physical activity and energy expenditure, particularly in rural areas where seasonal agricultural labour plays such an important role. We address this gap by integrating energy expenditure data derived from wearable tri-axial accelerometers with time-use data from conventional recall-based surveys. Using datasets from agricultural households in four rural communities in India and Nepal, our results show that there are significant gender differences in the patterns of time-use and energy expenditure. Men and women participate equally in productive work, however, women shoulder most of the additional reproductive work burdens in rural households at the expense of leisure opportunities. Our results provide insights into women’s responses to opportunities for productive work and highlight the nature of trade-offs they face.